Integrated mapping and characterization of the gene underlying the okra leaf trait in Gossypium hirsutum L - Zhu, Qian-Hao (Journal of experimental botany, 2016)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.